The Original Form of C4-Photosynthetic Phosphoenolpyruvate Carboxylase Is Retained in Pooids but Lost in Rice - Yamamoto, Naoki; Tong, Wurina; Lv, Bingbing; Peng, Zhengsong; Yang, Zaijun (Frontiers in Plant Science, 2022)
Poaceae is the most prominent monocot family that contains the primary cereal crops wheat, rice, and maize. These cereal species exhibit physiological diversity, such as different photosynthetic systems and environmental stress tolerance. Phosphoenolpyruvate carboxylase (PEPC) in Poaceae is encoded by a small multigene family and plays a central role in C4-photosynthesis and dicarboxylic acid metabolism. Here, to better understand the molecular basis of the cereal species diversity, we analyzed the PEPC gene family in wheat together with other grass species. We could designate seven plant-type and one bacterial-type grass PEPC groups, ppc1a, ppc1b, ppc2a, ppc2b, ppc3, ppc4, ppcC4, and ppc-b, respectively, among which ppc1b is an uncharacterized type of PEPC. Evolutionary inference revealed that these PEPCs were derived from five-types of ancient PEPCs (ppc1, ppc2, ppc3, ppc4, and ppc-b) in three chromosomal blocks of the ancestral Poaceae genome. C4-photosynthetic PEPC (ppcC4) had evolved from ppc1b, which seemed to be arisen by a chromosomal duplication event. We observed that ppc1b was lost in many Oryza species but preserved in Pooideae after natural selection. In silico analysis of cereal RNA-Seq data highlighted the preferential expression of ppc1b in upper ground organs, selective up-regulation of ppc1b under osmotic stress conditions, and nitrogen response of ppc1b. Characterization of wheat ppc1b showed high levels of gene expression in young leaves, transcriptional responses under nitrogen and abiotic stress, and the presence of a Dof1 binding site, similar to ppcC4 in maize. Our results indicate the evolving status of Poaceae PEPCs and suggest the functional association of ppc1-derivatives with adaptation to environmental changes.